Vocabulario Tagalo Tagalog-Spanish dictionary - San Antonio, Francisco de d.1624 (Pulong Sources for Philippine Studies, 2000)
A Tagalog-Spanish dictionary which is a reconstruction of the original manuscript of the early Tagalog-Spanish dictionary during the colonial era. This dictionary contains 7,000 entry words.